2020
DOI: 10.1111/hiv.13013
|View full text |Cite
|
Sign up to set email alerts
|

Caspofungin combined with TMP/SMZ as a first‐line therapy for moderate‐to‐severe PCP in patients with human immunodeficiency virus infection

Abstract: Objectives The effectiveness of trimethoprim/sulfamethoxazole (TMP/SMZ) for pneumocystis pneumonia (PCP) is limited with adverse events. Caspofungin, by inhibiting the cyst form of Pneumocystis jirovecii, may be an alternative therapy for PCP. However, the availability of clinical data about caspofungin combined with TMP/SMZ in the treatment of PCP in HIV‐infected patients is limited. Thus, we aimed to examine the clinical effectiveness and safety of caspofungin combined with TMP/SMZ as a first‐line therapy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
0
17
1
Order By: Relevance
“…With the increasing complexity of azole-based prophylaxis (e.g., drug-drug interactions), echinocandins have garnered attention for their potential in antifungal prophylaxis [ 38 , 39 ]. However, despite limited alternatives to standard TMP-SMX, micafungin, anidulafungin and CAS have not been recommended for prophylaxis against PCP based on in vivo efficacy [ 26 , 40 , 41 , 42 ]. The PK profile of rezafungin not only sets it apart from other echinocandins in traditional PK analysis; higher penetration of rezafungin at the infected tissue site, as observed compared with micafungin, may explain observed differences in efficacy compared with other echinocandins [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing complexity of azole-based prophylaxis (e.g., drug-drug interactions), echinocandins have garnered attention for their potential in antifungal prophylaxis [ 38 , 39 ]. However, despite limited alternatives to standard TMP-SMX, micafungin, anidulafungin and CAS have not been recommended for prophylaxis against PCP based on in vivo efficacy [ 26 , 40 , 41 , 42 ]. The PK profile of rezafungin not only sets it apart from other echinocandins in traditional PK analysis; higher penetration of rezafungin at the infected tissue site, as observed compared with micafungin, may explain observed differences in efficacy compared with other echinocandins [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of bioplausibility [ 50 ] and observational reports [ 51–53 ], there has been interest in the use of the echinocandins as adjunctive agents for the treatment of PCP. There are currently 2 randomized controlled trials in critically ill patients without HIV examining the use of adjunctive caspofungin listed as actively recruiting (ClinicalTrials.gov Identifier NCT03978559 and NCT02603575); however, the use of echinocandins in patients with HIV and/or before critical illness will need to be inferred from those results unless additional trials are conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Previous case reports showed that the efficacy of caspofungin was favorable when it was used as a first-line drug or for salvage therapy for PCP [ 19 ]. A trial involving the caspofungin salvage therapy for PCP showed a high success rate (80%) among HIV-infected patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%